Alleviation of dextran sulfate sodium (DSS)-induced colitis in mice through the antioxidative effects of muscone via the MyD88/p38 MAPK signalling pathway - Gang Yao; Jian Zhang; Lingyan Zhang; Hai Zhao; Shuguang Wu; Hongmei Yang; Jiangwei Yu (PeerJ)
Background Inflammatory bowel disease (IBD) is characterized by chronic inflammation. Ulcerative colitis (UC) is a subtype of IBD. The symptoms of UC include inflammation, damage to crypts, and ulceration. UC patients frequently experience comorbid psychological disorders. Muscone has notable anti-inflammatory, antioxidative, and antidementia properties. Our study aimed to investigate the potential of muscone to alleviate colitis, the underlying mechanisms, and the signalling pathways involved. Methods C57BL/6 mice were administered dextran sulfate sodium (DSS) to induce colitis. The SMART v3.0 (Panlab, Barcelona, Spain) was used to measure parameters in the open field test and the tail suspension test to assess depression and anxiety. Gait changes were analysed using the DigiGait™ imaging system. The severity of colitis was assessed through body weight loss, stool consistency, gross bleeding, and histopathological evaluation. Proteins related to anti-inflammatory and antioxidative effects were analysed in dissociated tissues using mouse-specific commercial enzyme-linked immunosorbent assay (ELISA) kits. Results Muscone treatment reduced gross bleeding and histopathological damage scores and increased the ratio of colon length to body weight. Gait analysis revealed improvements in swing time, brake time, propulsive time, stance duration, stride duration, stride length, stride frequency, and paw area with muscone treatment. However, muscone treatment did not improve the distance travelled or the time spent in the open field test, nor did it affect the immobility duration in the tail suspension test. We observed that the expression of claudin-1, occludin, and zonula occludens-1 (ZO-1) increased in response to treatment with muscone. Muscone treatment downregulated the expression of interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-17 (IL-17), interleukin-33 (IL-33), and tumour necrosis factor-α (TNF-α), while increasing the expression of interleukin-4 (IL-4) and interleukin-10 (IL-10). Muscone treatment increased the concentrations of catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-PX), and haem oxygenase (HO-1), and suppressed the expression of myeloperoxidase (MPO), cyclooxygenase-2 (COX-2), and nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOX1 and NOX2). Furthermore, muscone treatment inhibited the expression of myeloid differentiation primary response 88 (MyD88) and p38 mitogen-activated protein kinase (MAPK). Conclusion Muscone effectively alleviated the symptoms of colitis, which may be due to the reduction in reactive oxygen species (ROS). The potential mechanism underlying the mitigation of colitis may involve the inhibition of the MyD88/p38 MAPK signalling pathway. Our studies suggest that muscone could be a promising target for treating IBD in clinical studies.